Relationship between head nurses' transformational leadership style and attitudes toward reporting patient safety incidents in Hospitals - Pamela, Cyrilla Ayu; Ahsan, Ahsan; Wardhani, Viera (Alma Ata University Press, 2025)
Background : Patient safety is a top priority in healthcare services to prevent avoidable incidents and reduce the risk of medical errors. The World Health Organization (WHO) reports that patient safety incidents are among the top ten leading causes of death and disability worldwide. However, the reporting rate for patient safety incidents remains low, reflecting a weak safety culture in hospitals. One factor influencing healthcare professionals' attitudes toward reporting patient safety incidents is leadership style. Transformational leadership is believed to enhance motivation, proactive behavior, and strengthen the safety culture in hospital settings.Objectives : This study aims to analyze the relationship between head nurses' transformational leadership style and attitudes toward reporting patient safety incidents in the inpatient wards of Kanjuruhan Regional General Hospital, Malang.Methods : This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 154 nurses working in inpatient wards, selected through purposive sampling. The research instruments included the Multifactor Leadership Questionnaire (MLQ) to assess transformational leadership and a questionnaire on attitudes toward patient safety incident reporting. Data analysis was conducted using the Spearman Rank correlation test, with a significance level of p < 0.05.Results : The findings revealed that transformational leadership had a mean score of 4.03 (SD = 0.504), while attitudes toward patient safety incident reporting had a mean score of 3.94 (SD = 0.429). Spearman Rank correlation analysis showed a significant positive relationship between transformational leadership and attitudes toward patient safety incident reporting (p = 0.000, r = 0.523). This indicates that the higher the implementation of transformational leadership by the head nurse, the more positive the nurses' attitudes toward reporting patient safety incidents.Conclusions : Transformational leadership plays a crucial role in improving attitudes toward patient safety incident reporting and fostering a stronger safety culture in hospitals. Therefore, leadership training for head nurses and the reinforcement of a non-punitive incident reporting system are necessary to enhance healthcare professionals' engagement in incident reporting.